Credible distributed identity authentication system of microgrid based on blockchain - Guanqun YANG; Yin LIU; Hao XU; Hongwei XING; Jianhui ZHANG; Entang LI (网络与信息安全学报)
Most of the blockchain-based identity authentication systems are based on public blockchain, which are still essentially traditional centralized identity management and verification methods, making it difficult to meet the needs of trusted access and fine-grained access control in microgrids.Therefore, based on the FISCO BCOS consortium blockchain technology, a distributed identity authentication system supporting multi-center was designed.A DID-based identity management protocol to achieve autonomous control of user identity in a practical scenarios was designed.Distributed trusted access technology for end nodes in microgrids was studied, and privacy-protecting credentials based on zero-knowledge proof were designed.This scheme meets the requirements of trustworthy and verifiable user identity in different privacy security scenarios, and achieves autonomous control of entity identity, fine-grained access control and trusted data exchange.The usability and effectiveness of the proposed algorithm are demonstrated through system experiments and performance analysis.